Learning Outcomes and School Cost-Effectiveness in Mexico : The PARE Program - López Acevedo, Gladys (The World Bank, 1999)
May 1999 - Roughly doubling the school resources allocated per student overcame a 30 percent deficit in test scores among rural students in Mexico's PARE program. Past research often attributed most differences in student learning to socioeconomic factors, implying that the potential for direct educational interventions to reduce learning inequality was limited. Acevedo shows that learning achievement can be improved through appropriately designed and reasonably well-implemented interventions. She studies the impact of the Programa para Abatir el Rezago Educativo (PARE), a program designed to improve the quality and efficiency of primary education in four Mexican states by improving school resources. The PARE program increased learning achievement in rural and native schools, where students had typically not performed as well as other students (in Spanish). Not only did students' cognitive abilities improve under the PARE program, but the probability of their continuing in school improved. In rural areas where the PARE design was fully implemented, test scores for the average student increased considerably. A 30 percent deficit in test scores among rural students could be overcome by roughly doubling the resources allocated per student. This paper-a product of the Mexico Country Management Unit, Latin America and the Caribbean Region-is part of a larger effort in the region to understand the impact of program intervention in Mexico. The author may be contacted at gacevedo@worldbank.org